Analysis of the low motor activity of students of the specialized educational department - Gryban G.P (Kharkov National Pedagogical University, 2012)
The paper highlights the results of investigations into the reasons for the low motor activity of students who belong to a special medical group due to their state of health. Deals with the gap between huge amount of mental activity and insufficient motor activity. The absence of dosed motor activity has it's negative impact on students' health, reduces their labor activity and the quality of educational process. The combination of physical exercises provide healthy and training effect on the students who have health condition aberrations.